Quantification of uncertainty of performance measures using graph theory - Lopes, Isabel da Silva (2013)
In this paper, the graph theory is used to quantify the uncertainty generated in performance measures during the process of performance measurement. A graph is developed considering all the sources of uncertainty present in this process and their relationship. The permanent function of the matrix associated with the graph is used as the basis for determining an uncertainty index.